(untitled) (UTM Press - Edited Book, 2025)
Malaysia’s Sustainable Pathways is a comprehensive exploration of the nation’s journey towards sustainable development, emphasising economic, social, and corporate dimensions. The book is structured into six insightful chapters, each addressing a critical aspect of sustainability. Chapter 1, “Malaysia’s Sustainable Development,” provides an overview of how Malaysia balances economic expansion with environmental preservation, aiming for a sustainable future. Chapter 2, “Bridging the Divide: Tackling Income Inequality in Malaysia,” examines the socioeconomic challenges and initiatives to reduce income disparities, highlighting the importance of equity in sustainable development. Chapter 3, “Sustaining the Plate: Food Security in Malaysia,” focusses on the critical issue of food security and its implications for socioeconomic well-being, discussing strategies to ensure a stable food supply. Chapters 4, 5, and 6 delve into corporate sustainability. Chapter 4, “Sustainability Management Accounting Practices in the Malaysian Electrical Industry,” explores how businesses integrate sustainability into their financial practices. Chapter 5, “Revealing Disclosure Strategies: An Analysis of Corporate SDG Engagement,” analyses corporate commitments to the Sustainable Development Goals (SDGs). Chapter 6, “Navigating Sustainability in the Halal Industry: A Manufacturer’s Dilemma,” discusses the unique sustainability challenges faced by the halal industry. This book is targeted at policymakers, business leaders, academics, and students interested in sustainable development, providing a detailed roadmap for achieving a balanced and sustainable future in Malaysia.